RESEARCH ACTIVITIES IN THE EUROPEAN QUALIFICATIONS SYSTEM: EXPERIENCE AND PROBLEMS - O. V. Vorobieva; I. G. Teleshova (Высшее образование в России)
The article considers the European experience of implementing scientific/research activities and the formation of a framework of qualifications for research career. The authors define and analyze the stages of this process revealing the special role of the Bologna and Copenhagen strategies and the documents and programs developed by them and give examples of creating specialized, sectoral and institutional frameworks within the European Research Area. Particular attention is paid to the methodological culture of creating qualification frameworks, difficulties in distinguishing levels and finding an adequate language for their description. The question is raised about topical problems in the process of forming the sectoral framework in the field of Education and Science in Russia and implementation of European experience in our country. The European experience shows that the process of qualification framework formation in the spheres of education and science requires the system approach, involvement of all the parties concerned, an overall and thorough discussion of the alignment process on all the levels of qualification. It is worth drawing attention to the framework character of the qualification system. It should be viewed more as guidance, incentive, strategy rather than a binding legal instrument. The most difficult issues concern the structure and content of this framework (what should be the levels of research activities description, how to categorize the descriptors, what are the criteria for assessment of quality of scientific/research activities according to researcher’s rank and other issues).